Direct evidence of Toxoplasma-induced changes in serum testosterone in mice - Kaňková, Sárka; Kodym, Petr; Flegr, Jaroslav (Experimental parasitology, 2011)
Latent toxoplasmosis is known to influence the morphology of infected persons and also increases the probability of the birth of male offspring in both humans and mice. All these traits can be related to the observed differences in the concentration of testosterone between Toxoplasma-infected and Toxoplasma-free subjects. However, it is not possible to decide, using the Toxoplasma-human model, whether toxoplasmosis influences the level of testosterone in the infected host or whether individuals with different levels of testosterone vary in the probability of toxoplasma infection. Here we studied changes in the testosterone levels in the latent phase of toxoplasmosis in laboratory mice artificially infected with cystogenic but relatively virulent strain T38 of T. gondii. We observed decreased testosterone levels in both female and male mice with latent toxoplasmosis in comparison to uninfected controls (P=0.001). The present results indicate that Toxoplasma infection changes the concentration of serum testosterone in mice and human rather than changed concentration of testosterone influences the probability of the Toxoplasma infection. It is possible that the decrease of testosterone is an adaptive mechanism of infected mice aimed to compensate toxoplasmosis-induced immunosuppression observed during latent Toxoplasma infection.
Keywords: modely nemocí na zvířatech; Male; sexuální faktory; myši inbrední BALB C; toxoplazmóza; mužské pohlaví; Mice, Inbred BALB C; Animals; Toxoplasmosis; ženské pohlaví; zvířata; Sex Factors; testosteron; myši inbrední C57BL; Disease Models, Animal; myši; Mice, Inbred C57BL; Mice; Female; Testosterone